ONGROWING TECHNIQUES FOR JUVENILE DONKEY EAR ABALONE (HALIOTIS ASINIA) AT PEMENANG WATERS, NORTH LOMBOK, INDONESIA - Setyono, Dwi Eny Djoko; Aswandy, Indra (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2010)
Abalone is one of the most prized sea delicacies in the world. In Indonesia, although donkey ear abalone (Haliotis asinina) forms a valuable fishery, little is known about its culture techniques. A study has been conducted to find out the most suitable technique for ongrowing donkey ear abalone, for to the local farmer in Indonesia. Juveniles used in study were collected from the southern Lombok coastal waters. They were reared in different type of structure (CNC = circular net cage and TNC = tyre net cage) and set at different depths. Juveniles were fed ad-libitum by macroalgae, Gracilaria spp. Results of the study showed that juveniles of donkey ear abalone have a better growth when cultured offshore in a TNC than in CNC. To gain a better growth, juveniles abalone need to be reared in cages which provided more shelter and less light. Donkey ear abalone was considered a hardy species, survival rate was not influenced by the type of structure (CNC or TNC) and setting position (depths).